Spy catcher - "Wright, Peter" (New York, 1987)
The former assistant director of MI5 offers an account of British Intelligence, including his work on the Ring of Five and exposing Soviet espionage and the conspiracy to oust Harold Wilson from the office of Prime Minister in the 1970s.
Keywords: "Wright, Peter Biography"